Black talc-based medical antibacterial gauze and preparation method thereof

Through the manganese antibacterial antibacterial agent that adheres to the surface of black slippery stones on the surface of the medical non -woven fabric to form a black slippery stone -based medical antibacterial gauze, the problem of poor traditional gauze antibacterial properties is solved, and the rapid healing and low scar formation of the wound is achieved.

CN119345430APending Publication Date: 2025-01-24CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411438090.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Traditional medical gauze has poor antibacterial properties, which can easily lead to wound infection, and it is difficult to promote rapid healing of wounds during the healing process, which may lead to scar formation.

Method used

Using black talc as a carrier, manganese oxide is synthesized in situ through hydrothermal reaction to prepare an antibacterial agent, which is adhered to a medical non-woven fabric to form a black talc-based medical antibacterial gauze.

Benefits of technology

Improve the antibacterial performance and biocompatibility of gauze, promote the rapid healing of the wound, reduce the formation of scars, and reduce the risk of wound infection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119345430A_ABST
    Figure CN119345430A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of medical antibacterial gauze, in particular to black talc-based medical antibacterial gauze and a preparation method thereof. According to the black talc-based medical antibacterial gauze, a medical non-woven fabric is used as a carrier to load an antibacterial agent, the antibacterial agent comprises black talc and manganese oxide loaded on the surface of the black talc, and the manganese oxide comprises Mn3O4 and MnOOH. The black talc-based manganese oxide antibacterial agent prepared by the invention has the characteristics of high antibacterial property, low cytotoxicity, low hemolysis and the like. The black talc-based medical antibacterial gauze provided by the invention has high antibacterial property and biocompatibility, promotes accelerated healing of wounds from an early stage, can effectively promote wound healing, can greatly shorten the wound time, increases wound cell proliferation, enhances tissue connectivity, reduces granulation tissue area, and is more advanced and mature in skin regeneration; the formation of scars is reduced; the problem that traditional medical gauze is poor in antibacterial property is solved, and the medical gauze can be effectively used for healing skin wounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical antibacterial gauze, in particular to a black talc-based medical antibacterial gauze and a preparation method thereof. Background Art

[0002] Skin is the first barrier to protect the human body from harm. In daily life, people will inevitably encounter various accidents that cause skin damage. In the process of healing, damaged skin is very susceptible to bacterial infection in the environment, which can easily cause the wound to deteriorate. In severe cases, it can cause systemic sepsis, phlebitis, and even death.

[0003] Traditional gauze has poor antibacterial properties due to its high permeability, and usually requires the use of antibiotics, which can easily lead to the birth of drug-resistant bacteria and has almost no effect on promoting healing of the wound surface. In addition, most functional gauze is either complicated to make and costly, or simple in method but with insignificant therapeutic effects, and scars are likely to form after the wound heals. Summary of the invention

[0004] The purpose of the present invention is to provide a black talc-based medical antibacterial gauze and a preparation method thereof in view of the above-mentioned deficiencies in the prior art.

[0005] The invention discloses a black talc-based medical antibacterial gauze, which uses a medical non-woven fabric as a carrier to load an antibacterial agent. The antibacterial agent comprises black talc and manganese oxide loaded on the surface of the black talc. The manganese oxide comprises Mn3O4 and MnOOH.

[0006] Furthermore, the preparation method of the antibacterial agent is: using potassium permanganate, urea and hexadecyltrimethylammonium bromide as raw materials, adopting a hydrothermal reaction in-situ synthesis method, loading manganese oxide on the surface of black talc, and obtaining the antibacterial agent.

[0007] Furthermore, the temperature of the hydrothermal reaction is 150-190°C.

[0008] Further, the purity of the black talc is 70-85%.

[0009] Furthermore, black talc is dissolved in a certain amount of KMnO4 and urea solution, and then CTAB is added to the mixed solution and stirred in a water bath, and a hydrothermal reaction is carried out at 150-190°C. After the reaction is completed, it is filtered, dried and cooled to room temperature, and then taken out and fully ground to obtain a powder sample, i.e., the antibacterial agent.

[0010] Furthermore, the mass ratio of black talc to KMnO4 is 0.4-0.8.

[0011] Further, the mixture was stirred in a water bath at 60-80°C for 30 min.

[0012] Further, drying at 60-80°C is performed and cooled to room temperature.

[0013] A method for preparing the above-mentioned black talc-based medical antibacterial gauze comprises the following steps:

[0014] S1: preparation of antimicrobial agent;

[0015] S2: preparing the antimicrobial agent into a suspension;

[0016] S3: Immerse the medical nonwoven fabric in the evenly stirred suspension, soaking the upper and lower edges once each;

[0017] S4: Press and dry the soaked gauze to obtain kaolin hemostatic gauze.

[0018] Furthermore, the concentration range of the antimicrobial suspension is 0.25-1.5 g / L.

[0019] The antibacterial agent of the present invention utilizes the layered structure of the unique black talc, and synthesizes manganese oxide on the surface of the black talc by liquid phase in-situ synthesis method. The crystal phase and morphology of manganese oxide are controlled by adding black talc and regulating the synthesis temperature; high temperature and the addition of talc are conducive to the conversion of Mn3O4 to MnOOH. The material can not only improve the stability of manganese oxide, reduce aggregation, and have high antibacterial properties, but also enhance its biocompatibility, have the characteristics of low cytotoxicity, low hemolysis, etc., and is suitable for various biomedical occasions.

[0020] The black talc-based medical antibacterial gauze of the invention consists of medical gauze and an antibacterial agent adhered to the medical gauze, and the gauze has high antibacterial property and biocompatibility.

[0021] The black talc-based medical antibacterial gauze of the present invention promotes accelerated wound healing from an early stage, can effectively promote wound healing, can greatly shorten the time of wound healing, and increases wound cell proliferation, enhances tissue connectivity, reduces granulation tissue area, makes skin regeneration more advanced and mature, and reduces scar formation; it improves the problem of poor antibacterial property of traditional medical gauze and can be effectively used for the healing of skin wounds.

[0022] The black talc-based medical antibacterial gauze of the present invention has higher hydrophilicity and can absorb wound exudate more effectively, thereby providing enhanced antibacterial protection and reducing the risk of wound infection.

[0023] The preparation method of the black talc-based medical antibacterial gauze of the invention is simple, and is easy to realize large-scale production, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 XRD patterns of samples prepared in Examples 1-3 and Comparative Examples 1-3;

[0025] Figure 2 XPS graphs of samples prepared in Examples 1-3 and Comparative Examples 1-3;

[0026] Figure 3 The SEM images of Examples 1-3 and Comparative Examples 1-3 are shown;

[0027] Figure 4 TEM of Examples 1-3 and Comparative Examples 1-3;

[0028] Figure 5-Figure 10 It is a statistical chart of the antibacterial performance test and biosafety test results of Comparative Examples 1-3 and Examples 1-3;

[0029] Fig.11 The SEM image of Example 3 (M / T-190) and bacteria;

[0030] Fig.12 The present invention is a flow chart of the preparation of black talc-based medical antibacterial gauze;

[0031] Fig.13 The following are the actual photos of unloaded gauze, black talc loaded gauze, M-190 loaded gauze, and M / T-190 loaded gauze;

[0032] Fig.14 The contact angle test results of unloaded gauze, black talc loaded gauze, M-190 loaded gauze, and M / T-190 loaded gauze;

[0033] Fig.15 The SEM morphology and Mn distribution of unloaded gauze, black talc loaded gauze, M-190 loaded gauze, and M / T-190 loaded gauze;

[0034] Fig.16 This is a flow chart for wound healing experiments;

[0035] Fig.17 Capture digital images during wound healing experimental studies;

[0036] Fig.18 This is a statistical chart of the relative wound area in the wound healing experiment;

[0037] Fig.19 This is a graph showing the weight changes of mice in the wound healing experiment;

[0038] Fig. 20 Figure 2 is a histological analysis. DETAILED DESCRIPTION

[0039] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0040] Example 1

[0041] In this example, M / T-150 was prepared. 0.79g KMnO4 and 0.075g urea were added to 20mL deionized water, followed by 0.225g CTAB dissolved, 0.5g black talc added, and heated in a 60°C water bath for 30min. After taking it out, it was transferred to a hydrothermal reactor and hydrothermally heated at 150°C. After the reaction was completed, it was filtered, dried at 60-80°C and cooled to room temperature, taken out and fully ground to obtain a powdered sample. M / T-150 was obtained.

[0042] Example 2

[0043] In this example, M / T-170 was prepared. 0.79g KMnO4 and 0.075g urea were added to 20mL deionized water, followed by 0.225g CTAB dissolved, 0.5g black talc added, and heated in a 60°C water bath for 30min. After taking it out, it was transferred to a hydrothermal reactor and hydrothermally heated at 170°C. After the reaction was completed, it was filtered, dried at 60-80°C and cooled to room temperature, taken out and fully ground to obtain a powdered sample. M / T-170 was obtained.

[0044] Example 3

[0045] In this example, M / T-190 was prepared. 0.79g KMnO4 and 0.075g urea were added to 20mL deionized water, followed by 0.225g CTAB dissolved, 0.5g black talc added, and heated in a 60°C water bath for 30min. After taking it out, it was transferred to a hydrothermal reactor and hydrothermally heated at 190°C. After the reaction was completed, it was filtered, dried at 60-80°C and cooled to room temperature, taken out and fully ground to obtain a powdered sample. M / T-190 was obtained.

[0046] Comparative Example 1

[0047] This comparative example prepares M-150. Take 0.79g KMnO4 and 0.075g urea, add them to 20mL deionized water, then add 0.225g CTAB to dissolve, put it into a 60℃ water bath and heat it for 30min, take it out and transfer it to a hydrothermal reactor, and perform hydrothermal treatment at 150℃. After the reaction is completed, filter it, dry it at 60-80℃ and cool it to room temperature, take it out and grind it thoroughly to obtain a powdered sample. M-150 is obtained.

[0048] Comparative Example 2

[0049] This comparative example prepares M-170. Take 0.79g KMnO4 and 0.075g urea, add them to 20mL deionized water, then add 0.225g CTAB to dissolve, put it into a 60℃ water bath and heat it for 30min, take it out and transfer it to a hydrothermal reactor, and perform hydrothermal at 170℃. After the reaction is completed, filter it, dry it at 60-80℃ and cool it to room temperature, take it out and grind it thoroughly to obtain a powdered sample. M-170 is obtained.

[0050] Comparative Example 3

[0051] This comparative example prepares M-190. Take 0.79g KMnO4 and 0.075g urea, add them to 20mL deionized water, then add 0.225g CTAB to dissolve, put it into a 60℃ water bath and heat it for 30min, take it out and transfer it to a hydrothermal reactor, and perform hydrothermal treatment at 190℃. After the reaction is completed, filter it, dry it at 60-80℃ and cool it to room temperature, take it out and grind it thoroughly to obtain a powdered sample. M-190 is obtained.

[0052] Antibacterial property test: Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) were grown in 5 ml of Luria-Bertani (LB) broth at 37°C for 4 hours. The bacterial culture was then diluted to 10 4 Up to 10 5 times to a concentration of about 10 6 CFU / mL. Different concentrations of antimicrobial materials (M-150, M-170, M-190, M / T-150, M / T-170, M / T-190) were added to the bacterial suspension and their antimicrobial effects were evaluated by plate count technique. The bacterial growth inhibition rate was determined by comparing the colony counts of the test samples and the control group.

[0053] Biosafety test: 1. Cytotoxicity: The cytotoxic effect of the composite material on BJ cells was determined by direct contact method. BJ cells were placed in 1640 medium rich in 10% fetal bovine serum and 1% penicillin / streptomycin, and cultured for three days in an environment of 5% CO2 at a temperature of 37°C. The samples were then placed in a 96-well plate and cultured for 24 hours. After the culture, 100 μL of CCK-8 (cell proliferation and toxicity detection kit) reagent was added to each well, and then cultured for another hour at 37°C. The absorbance at a wavelength of 450nm was measured using a plate reader to calculate the cell survival rate; 2. Hemolysis: Fresh rabbit blood treated with anticoagulants was rinsed with phosphate buffer to prepare a 5% red blood cell suspension. An equal amount of 500 μL of composite material solution was mixed with an equal amount of red blood cell suspension and cultured at 37°C for one hour. Phosphate buffer and water were used as negative and positive controls, respectively. After centrifugation, the supernatant was collected, and the absorbance was measured at a wavelength of 545nm using a microplate reader to calculate the hemolysis rate.

[0054] The results of antibacterial performance test and biosafety test are shown in Table 1 and Figure 5-Figure 10 shown.

[0055] Table 1. Biological properties of examples and comparative examples

[0056]

[0057]

[0058] As can be seen from the above table, the antibacterial properties of the M / T-150 material prepared in Example 1 at a concentration of 0.50 mg / mL are 88.67% (E. coli) and 82.56% (S. aureus); the cell survival rate at a concentration of 0.025 mg / mL is 59.29%; and the hemolysis rate at a concentration of 0.10 mg / mL is 18.12%.

[0059] The antibacterial properties of the M / T-170 material prepared in Example 2 at a concentration of 0.50 mg / mL were 94.85% (E. coli) and 94.05% (S. aureus); the cell survival rate at a concentration of 0.025 mg / mL was 68.80%; and the hemolysis rate at a concentration of 0.10 mg / mL was 19.03%.

[0060] The antibacterial properties of the M / T-190 material prepared in Example 3 at a concentration of 0.50 mg / mL were 96.56% (E. coli) and 99.45% (S. aureus); the cell survival rate at a concentration of 0.025 mg / mL was 84.13%; and the hemolysis rate at a concentration of 0.10 mg / mL was 1.79%.

[0061] The antibacterial properties of the M-150 material prepared in Comparative Example 1 at a concentration of 0.50 mg / mL were 95.36% (E. coli) and 93.21% (S. aureus); the cell survival rate at a concentration of 0.025 mg / mL was 41.87%; and the hemolysis rate at a concentration of 0.10 mg / mL was 95.61%.

[0062] The antibacterial properties of the M-170 material prepared in Comparative Example 2 at a concentration of 0.50 mg / mL were 81.21% (E. coli) and 84.69% (S. aureus); the cell survival rate at a concentration of 0.025 mg / mL was 48.08%; and the hemolysis rate at a concentration of 0.10 mg / mL was 111.52%.

[0063] The antibacterial properties of the M-190 material prepared in Comparative Example 3 at a concentration of 0.50 mg / mL were 95.92% (E. coli) and 93.05% (S. aureus); the cell survival rate at a concentration of 0.025 mg / mL was 58.92%; and the hemolysis rate at a concentration of 0.10 mg / mL was 55.58%.

[0064] Figure 1 XRD of samples prepared in Examples 1-3 and Comparative Examples 1-3. The Mn oxides in the Examples and Comparative Examples are mixtures of Mn3O4 and MnOOH.

[0065] Figure 2 XPS analysis of samples prepared in Examples 1-3 and Comparative Examples 1-3, the proportion of Mn valence states in the XPS analysis of the Examples and Comparative Examples, wherein the addition of black talc leads to an increase in the content of high-valence Mn (IV). At the same synthesis temperature, the addition of black talc increases the higher valence state, indicating that black talc has a regulating effect on the formation of MnOOH and Mn3O4, affecting the valence state distribution of Mn.

[0066] Figure 3 The SEM images of Examples 1-3 and Comparative Examples 1-3 show that MnOx alone has a rod-like morphology, and the higher the temperature, the larger the rods. The addition of black talc causes the rod-like MnOx to be converted into irregular nanoparticles. M / T-150 is a smaller nanowire, M / T-170 is a mixture of nanorods and nanoparticles, and M / T-190 is the most significant with most of the particles being irregular nanoparticles.

[0067] Figure 4 The TEM morphology and crystal phase analysis of Examples 1-3 and Comparative Examples 1-3. The main crystal phase observed for M-150 is Mn3O4, and the main crystal phase observed for M-170 and M-190 is Mn3O4. A mixed crystal phase of Mn3O4 and MnOOH is observed; the main crystal phase observed for M / T-150 and M / T-170 is Mn3O4, and the main crystal phase observed for M / T-190 is MnOOH. The addition of black talc will lead to the stability of the MnOOH crystal phase at 190 degrees Celsius.

[0068] Figure 5 The biological performance and antibacterial performance statistics of comparative example 1 are shown in FIG. 1 ; the biological performance of comparative example 1 (M-150) is high in antibacterial effect, with each concentration being higher than 95%; the cell survival rate is low, all lower than 75%, and the hemolysis rate is high, all higher than 5%.

[0069] Figure 6 It is a statistical chart of the biological performance and antibacterial performance of Comparative Example 2; the biological performance of Comparative Example 2 (M-170) has high antibacterial effect, with each concentration being higher than 95%; the cell survival rate is low, all lower than 75%, and the hemolysis rate is high, all higher than 5%.

[0070] Figure 7 It is a statistical chart of the biological properties and antibacterial properties of Comparative Example 3; the biological properties of Comparative Example 3 (M-190) have high antibacterial effects, all concentrations are higher than 95%; the cell survival rate is low, less than 75% when the concentration is higher than 0.025, and the hemolysis rate is high, higher than 5% when the concentration is higher than 0.10.

[0071] Figure 8 The biological performance and antibacterial performance statistics of Example 1 are shown in the figure. The biological performance of Example 1 (M / T-150) shows that the antibacterial effect is average, which is higher than 95% when the concentration is lower than 0.5; the cell survival rate is average, which is lower than 75% when the concentration is higher than 0.025; the hemolysis rate is high, which is higher than 5% when the concentration is higher than 0.10.

[0072] Fig. 9 The biological performance and antibacterial performance statistics of Example 2 are shown in FIG. 1 . The biological performance of Example 2 (M / T-170) has a high antibacterial effect, which is higher than 95%; the cell survival rate is average, which is lower than 80% when the concentration is higher than 0.050; the hemolysis rate is high, which is higher than 5% when the concentration is higher than 0.10.

[0073] Fig.10 The biological performance and antibacterial performance statistics of Example 3 are as follows; the biological performance and antibacterial effect of Example 3 (M / T-190) are high, all higher than 95%; the cell survival rate is high, all higher than 75%, and the hemolysis rate is good, all higher than 5% when the concentration is higher than 0.20.

[0074] Fig.11 This is the SEM imaging of Example 3 (M / T-190) and bacteria. The morphology of the bacteria is deformed after the addition of M / T-190.

[0075] Example 4

[0076] 0.25g antibacterial agent prepared by embodiment 3 is added to 200mL water and stirred, and a piece of non-woven gauze (area is 10*9.5cm2) is cut out, and gauze is directly immersed in uniform suspension to make powder adhere to gauze surface, and the upper and lower sides of gauze are respectively soaked once, and the total duration is about 1min. The soaked gauze is placed on the roller press and suppressed once, and the upper and lower roller spacing of the roller press is 0.05mm, strengthens the adhesion degree of powder material and non-woven fabric. Finally, the non-woven gauze suppressed is hung in the air-dried in 60 ℃ baking oven with dovetail clips to obtain M / T-190 loaded gauze.

[0077] Comparative Example 4

[0078] The antibacterial agent in Example 4 was replaced by the antibacterial agent prepared in Comparative Example 3, and the rest was the same as in Example 4 to obtain M-190 loaded gauze.

[0079] Comparative Example 5

[0080] The antibacterial agent in Example 4 was replaced by black talc, and the other procedures were the same as those in Example 4 to obtain black talc-loaded gauze.

[0081] Fig.12 The present invention is a flow chart for the preparation of black talc-based medical antibacterial gauze.

[0082] Fig.13 These are actual photos of unloaded gauze (Gauze), black talc-loaded gauze (Talc@Gauze), M-190-loaded gauze (M@Gauze), and M / T-190-loaded gauze (M / T@Gauze).

[0083] Fig.14 The contact angle test results of unloaded gauze, black talc loaded gauze, M-190 loaded gauze, and M / T-190 loaded gauze are shown in Figure 2. The contact angle of M / T-190 loaded gauze is the smallest and has higher hydrophilicity. The enhanced hydrophilicity indicates that the composite gauze can absorb wound exudate more effectively, thereby providing enhanced antibacterial protection and reducing the risk of wound infection.

[0084] Fig.15 The SEM morphology and Mn distribution of unloaded gauze, black talc loaded gauze, M-190 loaded gauze, and M / T-190 loaded gauze. Fig.15 It can be seen that the surface of the gauze fiber without any loading is smooth, while the material can be seen attached to the composite gauze. Small flake structures can be seen attached to the gauze fibers in Talc@Gauze, rod-shaped particles are attached to the gauze fibers in M@Gauze, and rod-shaped particles and a large number of fine particles are attached to M / T@Gauze, which are mainly MnOx. This shows that the antibacterial agent is successfully loaded on the gauze.

[0085] Fig.16 Figure 1 is a flowchart of the wound healing experiment. Mice were divided into five treatment groups: saline (control group), unloaded gauze, black talc-loaded gauze, M-190-loaded gauze, and M / T-190-loaded gauze. Digital images (such as Fig.17 ) to monitor wound healing progress. M / T@Gauze promotes accelerated wound healing from an early stage.

[0086] Fig.18The relative wound area statistics of the wound healing experiment; M / T-190 loaded gauze (M / T@Gauze) promoted accelerated wound healing from the early stage, and a significant effect was observed on the 10th day. Quantitative analysis of the relative wound area confirmed that M / T-190 loaded gauze performed superiorly, with the wound area shrinking to near zero (0.57±2.29%) on the 14th day, significantly better than M@Gauze (1.23±2.28%), Talc@Gauze (9.52±2.87%), conventional gauze (15.67±6.47%) and the control group (26.84±21.44%). These results clearly show that M / T@Gauze has a higher wound healing ability than traditional treatment methods.

[0087] Fig.19 Figure 2 shows the weight changes of mice during the wound healing experiment; weight changes were monitored as an indirect indicator of wound healing progress. The groups treated with M@Gauze and M / T@Gauze showed improvements in wound healing and weight gain at the end of the study, highlighting the benefits of these treatments on overall health.

[0088] Fig. 20 For histological analysis, examination of wound tissue on day 14 showed increased cell proliferation, enhanced tissue connectivity, and reduced granulation tissue area in M / T@Gauze-treated wounds, all of which indicated accelerated tissue regeneration. In addition, Masson's trichrome staining showed that wounds treated with M / T@Gauze and M@Gauze had thicker, darker blue collagen fibers, indicating more advanced and mature skin regeneration. In contrast, wounds treated with Talc@Gauze and conventional gauze had thinner, lighter blue.

[0089] For matters not mentioned above, the prior art applies.

[0090] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A black talc-based medical antibacterial gauze, characterized in that: The medical non-woven fabric is used as a carrier to load an antibacterial agent, wherein the antibacterial agent comprises black talc and manganese oxide loaded on the surface thereof, and the manganese oxide comprises Mn3O4 and MnOOH.

2. The black talc-based medical antibacterial gauze according to claim 1, characterized in that: The preparation method of the antibacterial agent comprises the following steps: using potassium permanganate, urea and hexadecyltrimethylammonium bromide as raw materials, adopting a hydrothermal reaction in-situ synthesis method, and loading manganese oxide on the surface of black talc to obtain the antibacterial agent.

3. The black talc-based medical antibacterial gauze according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 150-190°C.

4. The black talc-based medical antibacterial gauze according to claim 2, characterized in that: The purity of black talc is 70-85%.

5. The black talc-based medical antibacterial gauze according to claim 2, characterized in that: The specific operation of the preparation method of the antibacterial agent is: dissolving black talc in a certain amount of KMnO4 and urea solution, then adding CTAB to the mixed solution and stirring in a water bath, performing a hydrothermal reaction at 150-190°C, filtering after the reaction, drying and cooling to room temperature, taking out and fully grinding to obtain a powdered sample, namely the antibacterial agent.

6. The black talc-based medical antibacterial gauze according to claim 5, characterized in that: The mass ratio of black talc to KMnO4 is 0.4-0.

8.

7. The black talc-based medical antibacterial gauze according to claim 5, characterized in that: Stir in a 60-80°C water bath for 30 min.

8. The black talc-based medical antibacterial gauze according to claim 5, characterized in that: Dry at 60-80℃ and cool to room temperature.

9. A method for preparing the black talc-based medical antibacterial gauze according to any one of claims 1 to 8, characterized in that: The steps include: S1: preparation of antimicrobial agent; S2: preparing the antimicrobial agent into a suspension; S3: Immerse the medical nonwoven fabric in the evenly stirred suspension, soaking the upper and lower edges once each; S4: Press and dry the soaked gauze to obtain kaolin hemostatic gauze.

10. The preparation method according to claim 9, characterized in that: The concentration range of the antimicrobial suspension is 0.25-1.5 g / L.